Urban water metabolism indicators derived from a water mass balance – Bridging the gap between visions and performance assessment of urban water resource management. (1st October 2017) - Renouf, M.A.; Serrao-Neumann, S.; Kenway, S.J.; Morgan, E.A.; Low Choy, D.
Abstract: Improving resource management in urban areas has been enshrined in visions for achieving sustainable urban areas, but to date it has been difficult to quantify performance indicators to help identify more sustainable outcomes, especially for water resources. In this work, we advance quantitative indicators for what we refer to as the 'metabolic' features of urban water management: those related to resource efficiency (for water and also water-related energy and nutrients), supply internalisation, urban hydrological performance, sustainable extraction, and recognition of the diverse functions of water. We derived indicators in consultation with stakeholders to bridge this gap between visions and performance indicators. This was done by first reviewing and categorising water-related resource management objectives for city-regions, and then deriving indicators that can gauge performance against them. The ability for these indicators to be quantified using data from an urban water mass balance was also examined. Indicators of water efficiency, supply internalisation, and hydrological performance (relative to a reference case) can be generated using existing urban water mass balance methods. In the future, indicators for water-related energy and nutrient efficiencies could be generated by overlaying the urban water balance with energy and nutrient data. Indicators of sustainable extraction and recognising diverse functions of water will require methods for defining sustainable extraction rates and a water functionality index. Highlights: There is a gap between the visions for urban water and performance assessment. Objectives for urban water management were categorised from industry visions. A set of indicators were derived for gauging performance against these objectives. Indicators can be quantified using data from an urban water mass balance. Other indicators are aspirational requiring further method development.